Understanding the Sustainable Hydrogen Generation Potential for the Region of Bavaria, Germany via Bio-Waste Processing Using Thermochemical Conversion Technology - Shashank Deepak Prabhu (Energies)
Future decarbonization targets demand a higher penetration of renewable energy (RE) sources into the system. However, challenges such as an uneven spatial and temporal distribution of various RE sources’ potential for green electricity (GE) generation demand alternative ways to store and later utilize the generated energy. In addition to that, sustainable development goals (SDGs) highlight the need for the responsible use of resources with increased recycling and a reduction in corresponding waste generation while ensuring access to affordable, reliable, sustainable, and modern energy for all. In this paper, an attempt is made to address both the issues of biodegradable waste (BW) processing and sustainable hydrogen (SH) production through it. Thermochemical conversion technology (TCC) and, within that, especially ‘thermocatalytic reforming’ (TCR®) technology have been explored as options to provide viable solutions. An added advantage of decentralized hydrogen production can be envisioned here that can also contribute to regional energy security to some degree. To analyze the concept, the Bavarian region in Germany, along with open-source data for bio-waste from two main sources, namely domestic household and sewage sludge (SS), were considered. Based on that, the corresponding regional hydrogen demand coverage potential was analyzed.